Some New Fixed-Point Theorems for a (𝜓,𝜙)-Pair Meir-Keeler-Type Set-Valued Contraction Map in Complete Metric Spaces - Chi-Ming Chen (Journal of Applied Mathematics)
We obtain some new fixed point theorems for a (𝜓,𝜙)-pair Meir-Keeler-type set-valued contraction map in metric spaces. Our main results generalize and improve the results of Klim and Wardowski, (2007).